Coronavirus Disease-2019 (COVID-19) and Cardiovascular Complications - Ma, Lulu (J Cardiothorac Vasc Anesth, 2021)
The coronavirus disease-2019 (COVID-19) has become a global pandemic. It has spread to more than 100 countries, and more than 1 million cases have been confirmed. Although coronavirus causes severe respiratory infections in humans, accumulating data have demonstrated cardiac complications and poor outcome in patients with COVID-19. A large percent of patients have underlying cardiovascular disease, and they are at a high risk of developing cardiac complications. The basics of the virus, the clinical manifestations, and the possible mechanisms of cardiac complications in patients with COVID-19 are reviewed. Before an effective vaccine or medicine is available, supportive therapy and identifying patients who are at high risk of cardiac complications are important.